1993
DOI: 10.1016/0014-5793(93)80082-6
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐activation of the murine dystrophin gene in human‐mouse hybrid myotubes

Abstract: Myotube cultures of the myogenic cell hne, C2, produce significantly lower levels of dystrophin than primary mouse cultures. We demonstrate that expression of the C2 dystrophin gene increases IO-fold in hybrid myotubes formed by fusion of C2 and dystrophin-deficient human myoblasts from a Duchenne muscular dystrophy patient. These results indicate that C2 cells are deficient in endogenous gene regulatory factors which enhance dystrophin expression, and that the C2 cell line may therefore be used to identify pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Thus, we can reasonably speculate that advantageous morphological and adhesive features of C2C12 cells would overcome some of the shortcomings of human cells, yielding vigorous contractility development of human-mouse hybrid myotubes under the culture conditions used in this study. Consistent with this interpretation, hybrid myotubes comprised of human-mouse 24 and human-cat 25 cells have also been studied, and malfunctions of human-origin muscle cells such as dystrophin-deficiency could reportedly be partially compensated for by forming hybrid myotubes with the non-human muscle cells.…”
Section: Discussionmentioning
confidence: 74%
“…Thus, we can reasonably speculate that advantageous morphological and adhesive features of C2C12 cells would overcome some of the shortcomings of human cells, yielding vigorous contractility development of human-mouse hybrid myotubes under the culture conditions used in this study. Consistent with this interpretation, hybrid myotubes comprised of human-mouse 24 and human-cat 25 cells have also been studied, and malfunctions of human-origin muscle cells such as dystrophin-deficiency could reportedly be partially compensated for by forming hybrid myotubes with the non-human muscle cells.…”
Section: Discussionmentioning
confidence: 74%
“…These results demonstrate that embryonic and fetal myoblasts will fuse with each other in vitro to form heterotypic myotubes, insofar as markers for each myoblast population can be found within individual myotubes. However, this should not be taken as proof that these myoblasts represent a common lineage; fusion of genetically distinct myoblasts from different species has previously been reported (Yaffe and Feldman, 1965;Pavlath et al, 1989;Noursadeghi et al, 1993). What this result does suggest is that there may be mechanisms at work in the developing embryo to inhibit the formation of heterotypic myotubes in vivo, because EM analysis of muscle development in vivo has shown that fetal myoblasts do not normally fuse with 1°m yotubes Harris et al, 1989).…”
Section: Discussionmentioning
confidence: 90%
“…Even though dystrophin was localized earlier to focal adhesions of cultured Xenopus laevis muscle cells (34) and in web-like surface structures of differentiated chicken myotubes (65), to our knowledge, this is a first report showing dystrophin localization at various adherens-type junctions in cultured muscle cells during reorganization of the actin cytoskeleton accompanying myogenesis. Earlier, it was reported that the original C2 mouse muscle cell line expresses only trace, if any, dystrophin (66,67). On the contrary, we have detected substantial amounts of dystrophin in the C2C12 subclone of C2 cells, therefore, allowing us to localize this protein during myodifferentiation in culture and to search for dystrophin-associated proteins in cultured muscle cells.…”
Section: Discussionmentioning
confidence: 51%